Evaluation of the body adiposity index in predicting percentage body fat among colombian adults (2015)
Objective: the body adiposity index (BAI) is a new simplistic method for predicting body fat percentage (BF%) via a simple equation of hip circumference to height. Up to now, few studies have evaluated the performance of BAI in determining excess fat in Colombians. The aim of this study was to evaluate the usefulness of BAI as a predictor of body fat in among Colombian adults. Methods: cross-sectional study carried out in a sample of 204 male belonging to the education sector from Bogotá, Colombia. BAI was calculated based on the equation reported in the Bergman et al. %BF determined by tetrapolar bioimpedance analysis (BIA) was used as the reference measure of adiposity. Bland-Altman analysis was used to assess the agreement between the two methods: BAI and BIA. Associations between anthropometric measures of adiposity were investigated by Pearson correlation analysis. Results: in general pupulation, the BAI overestimates %BF (mean difference: 12.5 % [95%CI = -4.04 % to -21.02 %]), mainly at lower levels of adiposity (mean difference: 10.2 ± 3.3). Significant correlations were found between BAI and all measurements, being the strongest-moderate correlation with %BF (r = 0.777, p less than 0.001), waist to height ratio (r = 0.557, p less than 0.001) and BMI (r = 0.480, p less than 0.001). Conclusion: the results of this investigation indicate that BAI results in large individual errors when predicting BF% among Colombian adults and has a tendency to provide overestimated values as BF% decreases. Therefore, this method can be a useful tool to predict %BF in Colombian adults, although it has some limitations. © 2015, Grupo Aula Medica S.A. All rights reserved.